Factors that Determine the Purchase of Portable Electronic Devices - GUIDI, ANTONIO CARLOS; PIZZINATTO, NADIA KASSOUF; MONTEBELO, MARIA IMACULADA (Revista de Negócios, 2020)
The study aims to discover the consumer profile and the main factors that lead them to acquire a portable electronic device (PED). An online survey was conducted, with a sample of 145 consumers involved in the beneficiation of the ornamental stone sector. Descriptive statistics, correlation analysis and multiple linear regression were applied for data analysis. This article makes advances in the development of concepts of management design, the electronic market and information systems, and uses a revised bibliography, proposing interaction with the list of strategies. The results show that, at the time of purchase, consumers of portable electronic devices take into account interconnected factors, such as brand, design and utility. Thus, we conclude that there is an interest in products that have proven multifunctionality, and also encourages research that confirms the consumer profile in expanded samples. The implications are discussed, with an emphasis on developing the new competencies that retailers need to develop, to interact with their physical configurations, through technological opportunities with mobile functionalities.